Factors Influencing the Psychological Well-Being of Psychiatric Nurses - et. al., Hwang Ye-won, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This descriptive survey study was conducted to define the factors influencing the psychological well-being of psychiatric nurses. For this study, a structuralized questionnaire was used. The subjects of this study were a total of 260 nurses who worked for over six months of clinical practice in 16 specialized psychiatric hospitals, psychiatric wards, and psychiatric hospitals in Korea. The data collected were analyzed using SPSS 21.0 and verified with descriptive statistics and Pearson’s correlation coefficient. In addition, a stepwise multiple regression analysis was used to determine the factors influencing the subjects’ psychological well-being. As a result, the scores of the psychiatric nurses' emotional labor, anger expression, and psychological well-being were 3.06 points, 23.04 points, and 3.41 points, respectively. Psychological well-being was revealed to have a significant negative correlation with emotional labor (r=-.25 p<.001), and anger expression (r=-.34 p<.001), its sub-factors: anger-in (r=-.36 p<.001), and anger-out (r= -.19 p=.003), and have a significant positive correlation with anger control (r=.12 p=.050). The factors found to affect psychological well-being were anger-in (β=-.30 p<.001) and anger control (β=.20 p<.001), which are sub-factors of anger expression, and mismatch of emotions, a sub-factor of emotional labor (β=-.16 p=.001). Therefore, it is necessary to identify important factors that affectthe psychological well-being of psychiatric nurses, and develop strategies to reduce the intensity of emotional labor, especially the mismatch of emotions, and effectively control anger expression.